AB0919 Validation of proteomic biomarkers observed in monozygotic twins confirms two proteins associated with psoriatic disease. (12th June 2018) - Generali, E.; Isailovic, N.; Ceribelli, A.; Sacrini, F.; De Santis, M.; Meroni, M.; Guidelli, G.M.; Caprioli, M.; Costanzo, A.; Selmi, C.
Abstract : Background: Skin psoriasis affects 3% of the general population and as much as 20%–40% of patients will develop psoriatic arthritis (PsA), with the two conditions representing a clinical and immunological continuum within a prototype for chronic inflammation. Different from most rheumatic diseases, no serum autoantibody is associated with PsA, and there are currently no biomarkers for an early diagnosis and prediction of PsA onset in psoriasis, frequently causing a delayed diagnosis. Monozygotic twins discordant for psoriasis/PsA represent a unique setting to investigate the influence of environmental and stochastic factors on disease phenotype. Through a high-throughput proteomic analysis (SomaLogic) we have previously identified a set of 13 proteins differentially expressed in the serum of monozygotic twins discordant for psoriatic disease. Objectives: To validate serum proteomic biomarkers of psoriatic disease using commercially available ELISA in monozygotic twins and in unrelated patients with psoriasis or PsA. Methods: Our study included sera from our cohort of monozygotic twins previously described and from 70 unrelated patients with psoriatic disease (psoriasis without PsA 34%–49%, PsA with/without psoriasis 36%–51%; women 46%, median age 52 years, interquartile range 41–59) followed at Humanitas Research Hospital, and 25 healthy subjects (52% women, median age 52 years, IQR 44–62). Candidate serum proteomic biomarkers obtained by SomaLogic analysis were validated using commercially available ELISA kits and proteins are herein anonymized due to a pending patent request. Results: We found a significant correlation between SomaLogic results in monozygotic twins and ELISA results in unrelated psoriatic cases in the serum levels of 2 proteins (figure 1), which are involved in inflammatory and immune response, and one has been previously reported in psoriatic plaques. Four proteins showed a significantly different expression between psoriasis and PsA versus controls, in particular two proteins have a potential role in disease pathogenesis, as protein #1 acts as cell-surface receptor and regulates differentiation, proliferation and survival of dendritic cells, while protein #2 is involved in regulation of UV radiation-induced apoptosis and protein folding. Conclusions: Two serum proteomic biomarkers, previously identified in a cohort of monozygotic twins discordant for psoriatic disease, can discriminate psoriatic disease, thus representing potential biomarkers of disease and possibly playing a pathogenetic role in disease. Disclosure of Interest: None declared